Novel Tu translation elongation factor, mitochondrial (TUFM) homozygous variant in a consanguineous family with premature ovarian insufficiency - Zhang, Jun; Zhou, Xing‐Yu; Wang, Ao; Lai, Yun‐Hui; Zhang, Xiao‐Fei; Liu, Xiao‐Tong; Wang, Zhe; Liu, Yu‐Dong; Tang, Shu‐Yan; Chen, Shi‐Ling (Clinical genetics, 2023)
Premature ovarian insufficiency (POI) is a clinical syndrome of ovarian dysfunction characterized by cessation of menstruation occurring before the age of 40 years. The genetic causes of idiopathic POI remain unclear. Here we recruited a POI patient from a consanguineous family to screen for potential pathogenic variants associated with POI. Genetic variants of the pedigree were screened using whole‐exome sequencing analysis and validated through direct Sanger sequencing. A homozygous variant in TUFM (c.524G>C: p.Gly175Ala) was identified in this family. TUFM (Tu translation elongation factor, mitochondrial) is a nuclear‐encoded mitochondrial protein translation elongation factor that plays a critical role in maintaining normal mitochondrial function. The variant position was highly conserved among species and predicted to be disease causing. Our in vitro functional studies demonstrated that this variant causes decreased TUFM protein expression, leading to mitochondrial dysfunction and impaired autophagy activation. Moreover, we found that mice with targeted Tufm variant recapitulated the phenotypes of human POI. Thus, this is the first report of a homozygous pathogenic TUFM variant in POI. Our findings highlighted the essential role of mitochondrial genes in folliculogenesis and ovarian function maintenance. A homozygous variant in TUFM was identified in a consanguineous family affected by premature ovarian insufficiency (POI), which was verified to cause mitochondrial dysfunction, ovarian reserve decline and infertility. To the best of our knowledge, this is the first report identifying TUFM as the causative gene for human POI.